2011
DOI: 10.26719/2011.17.6.546
|View full text |Cite
|
Sign up to set email alerts
|

Role of HFE gene mutations on developing iron overload in beta thalassaemia carriers in Egypt

Abstract: A case-control study aimed to determine the prevalence of C282Y, H63D and S65C mutations of the HFE gene in β-thalassaemia carriers and investigate their influence on iron absorption. A total of 41 β-thalassaemia carriers and 40 control subjects without haemoglobinopathies were screened for the C282Y, H63D and S65C mutations by polymerase chain reaction-restriction fragment-length polymorphism. The iron status in these subjects was studied and correlated with the HFE gene mutations. H63D, S65C and C282Y allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
8
0
2
Order By: Relevance
“…The role of H63D mutation polymorphism in β-thal major or carrier conditions has been studied in regions with a high incidence of H63D, such as in Southern Europe and Asia. Various studies have yielded conflicting conclusions (shown in Table 1): some studies from Italy, Portugal, India and Egypt suggested that iron overload might arise from the interacting effect of β-thal with homozygous or even heterozygous H 63 D mutations (13,(19)(20)(21)(22)(23); other reports from Italy, India, Thailand, Brazil and Spain indicated that the iron status was not related to the H63D mutation status (24)(25)(26)(27)(28)(29). The discrepancy may be due to the sample size, hereditary background variations in different racial populations, the sex ratio and the severity of thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…The role of H63D mutation polymorphism in β-thal major or carrier conditions has been studied in regions with a high incidence of H63D, such as in Southern Europe and Asia. Various studies have yielded conflicting conclusions (shown in Table 1): some studies from Italy, Portugal, India and Egypt suggested that iron overload might arise from the interacting effect of β-thal with homozygous or even heterozygous H 63 D mutations (13,(19)(20)(21)(22)(23); other reports from Italy, India, Thailand, Brazil and Spain indicated that the iron status was not related to the H63D mutation status (24)(25)(26)(27)(28)(29). The discrepancy may be due to the sample size, hereditary background variations in different racial populations, the sex ratio and the severity of thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,8 The interaction of HFE gene and β-globin gene mutations may have synergistic effect, increasing iron absorption and storage in β-thalassemia major patients. 9 The present study is designed to determine the association of HFE gene mutation in β-thalassemia major patients.…”
Section: Hfe Gene Mutations Have Been Frequently Detected Inmentioning
confidence: 99%
“…6,7,8 The interaction of HFE gene and β-globin gene mutations together may produce iron overload in β-thalassaemia major patients. 9 The present study aims to determine the influence of haemochromatosis mutations on iron overload in thalassaemia major patients.…”
Section: How To Cite This Articlementioning
confidence: 99%